Noticias Biográficas (1945)
Información biográfica de: José Acevedo Gómez, José María Espinoza, Luis Vargas Tejada, Josefa Acevedo de Gómez, El presbítero José Romualdo Cuervo, Joaquín Guarín, José Manuel Groot.